The Participation of Muslim Community in the Election of Mayor Bandar Lampung: A Study of Voters' Understanding of Women's Leadership in the Living Tafsir Study - Faizal; Khairullah; Farizal Makmun; Anisa Mawarni (Yayasan Payungi Smart Madani, 2024)
This article examined the basis for voters in the political contestation in the Bandar Lampung City government in 2020 in deciding their choice of female leadership candidates. The foundation in question is an understanding based on the concept of leadership in Islam, as indicated by the Koran and Hadith. This study would be highlighted by the Reviea wing of Ving tafsir, a relatively new Model of Al-Qur’an study in Al-Qur’an studies. The study findings show that the people of Bandar Lampung City, in electing female leaders, have brought to life the verses of the Koran about leadership, even though they have not memorized or understood the text textually. Meanwhile, the level of community participation in the Mayor of Bandar Lampung election for female leadership candidates was higher than for male leadership candidates. Eva Dwiyana won 66.67% of the votes, which surpassed 2 (two) male leadership candidates, namely Ryco Mendoza, who won 14.33 votes, and Yusuf Qohar, who won 25.88 votes. This participation is classified as independent participation with indicators of confidence in the work program, especially in the religious field, and an increasingly mature level of political education.